NILAI-NILAI PENDIDIKAN KARAKTER PADA TARI KIAMAT KERATUAN DARAH PUTIH - Saputra, Edo Yoga; Ariyani, Farida; Mustika, I Wayan (Jurnal Tiyuh Lampung: Pendidikan Bahasa dan Kebudayaan, 2023)
This study aims to describe the values of character education in the Kiamat Keratuan Darah Putih dance by knowing the meaning of the various movements in the dance. This research is a qualitative research with a descriptive approach. The object of this research is the variety of movements of the Kiamat Keratuan Darah Putih dance in Kuripan village, South Lampung. The data sources in the study are the results of observing the variety of dance movements of the Apocalypse through videos and other documents that contain the analysis of the research conducted. Data analysis techniques include analysis, data presentation, and conclusions. The results of research on the variety of dance movements of the Apocalypse show that this dance has character education values which are described in several varieties of dance movements of the Apocalypse. The variety of movements includes worship and kenui drift, the character education values contained in Kiamat dance can include, 1) Religious values, 2) Responsibility values, 3) Hard work values, 4) Discipline values, and 5) Communicative values.